Comparative analysis of metabolic, reproductive, and sub-clinical mastitis in pure Holstein-Friesian and Sahiwal-crossbred cows - S. M. Khan; R. U. Khan; S. Naz; I. A. Alhidary; N. K. Momand; R. Tiwari (Archives Animal Breeding)
This study assessed the metabolic, reproductive, and udder health profiles of pure Holstein-Friesian (HF) cows and their Sahiwal crossbreeds (F1, F2, F3) under sub-tropical conditions. A total of 180 dairy cows were evaluated over 8 weeks postpartum, focusing on milk yield, serum metabolites (glucose, cholesterol, triglycerides, calcium, cortisol, and progesterone), somatic cell count (SCC), and reproductive performance. F2 cows exhibited the highest milk yield, particularly by week 6, with an overall weekly yield of 183.9 L, while HF cows had the lowest yield at 140.3 L. Serum glucose levels were highest in F2 cows during week 5, and cortisol was significantly higher in F2 cows than in other breeds. However, no significant differences were observed in cholesterol or triglyceride levels across the breeds, suggesting consistent metabolic management. The SCC was significantly higher in pure HF cows, indicating a greater susceptibility to sub-clinical mastitis. Reproductive performance, measured by the postpartum estrus interval (PEI) and the interestrus interval (IEI), declined with increasing HF genetics, with F1 cows showing the best adaptation to local conditions. Progesterone levels were higher in F1 cows, supporting better luteal activity and ovarian resumption. The study concludes that crossbreeding HF with Sahiwal improves milk production and reproductive health while reducing the risk of mastitis, with F1 and F2 cows showing the most favorable outcomes.